Subtitling Standards in Norway - Awedyk, Witosław (Folia Scandinavica Posnaniensia, 2013)
The main objective of this paper is to present the specificity of the work of a Norwegian subtitler in view of the unique language situation in Norway. In addition to the challenges an audiovisual translator needs to face, a general description of the Norwegian language policy will be presented here.